Tari Merak Ponorogo Sebagai Sarana Pembelajaran Gerak Keseharian dan Alam dalam Tari Siswa SD - Lintang Ayu Fitriyani; Eko Rahmad Juniawan (Journal of Elementary School (JOES), 2022)
The use of local wisdom as a learning tool can motivate and foster an attitude of nationalism in students, so it is necessary to develop learning facilities from the use of local wisdom. This study aims to determine the potential of the Ponorogo peacock creation dance as a means of student learning about demonstrating daily and natural movements in dance by paying attention to the values ​​contained in the Ponorogo peacock dance, and its suitability with the characteristics of second grade elementary school students. This research is a qualitative descriptive research, with a case study approach. Data collection techniques used were observations of the Ponorogo peacock dance, interviews with dance creators and elementary school teachers, and literature review. The results of this study indicate that the Ponorogo peacock dance has the potential as a means of learning daily and natural movements in dance for second grade elementary school students. Ponorogo peacock dance as a local wisdom of Ponorogo Regency describes the behavior of peacocks in accordance with the learning theme in grade II elementary school, namely about the environment. There are various local wisdoms from Ponorogo Regency that can be used as a learning tool for students. This research has implications for the means of learning dance in elementary schools. Keywords: Learning Facilities, Elementary School, Dance Art, Ponorogo Peacock Dance